Does our career influence our level of selfishness?: applied study in Peru - Blossiers Dietrich, Sandra (2008)
This study examines the existence of the paradigm of the human being as an egoistic individual, within the empirical plane. The possibility of variation of the degree of altruism in people’s behavior is explored according to their careers. For this analysis, we have applied experimental economics in students of the last year of their education, in Business Administration, Economics, Medicine and Sociology; all of them within a similar socioeconomic position.Other researchers have found evidence that the professional careers have, to a certain extent, some influence on the altruistic behavior. In this context, we have found that the economists would be the professional group that presents less altruistic behavior within our sample.On the other hand, by the elaboration of this study, we pretend to analyse if the gender differences are a determining factor in the degree of altruism; nevertheless, we did not find any important differences.In addition to this, our work also explores the possible influence of the geographic factor. For this, we used as a sample the department of Ica, where we made the necessary investigations for the case. On this, the individuals from this zone present a superior index of mutual cooperation, in comparison with the individuals from Lima.